Comprehensive Safety Management and Assessment at Rugby Football Competitions - Tajima, T.; Chosa, E.; Kawahara, K.; Nakamura, Y.; Yoshikawa, D.; Yamaguchi, N.; Kashiwagi, T. (International Journal of Sports Medicine, 2014)
The present study aims to improve medical systems by designing objective safety assessment criteria for rugby competitions. We evaluated 195 competitions between 2002 and 2011 using an original safety scale comprising the following sections: 1) competence of staff such as referees, medical attendants and match day doctor; 2) environment such as weather, wet bulb globe temperature and field conditions; and 3) emergency medical care systems at the competitions. Each section was subdivided into groups A, B and C according to good, normal or fair degrees of safety determined by combinations of the results.Overall safety was assessed as A, B and C for 110, 78 and 7 competitions, respectively. The assessments of individual major factors were mostly favorable for staff, but the environment and medical care systems were assessed as C in 25 and 70, respectively, of the 195 competitions. Medical management involves not having a match day doctor, but also comprehensive management including preventive factors and responses from the staff, environment and medical-care systems. 6 cases of severe injuries and accidents occurred between 2002 and 2011, which were observed in Grade A competition. These cases revealed better prognosis without obvious impairment, thus confirming the value of the present assessment scale.
Keywords: medical-care system; environment; medical staff; rugby-football